Entrepreneurship Digitalization Effectiveness in Micro Small Medium Enterprises of the Food and Beverage Sector - Pahlawan, Princhita Nabila Maram (FEB - Universitas Lampung, 2025)
This research purpose is to analyze how imperative Entrepreneurship Digitalization be developed and the MSMEs’ challenges and opportunities to be taken. To address these purposes, a qualitative research design was employed through semi-structured interviews. Interviews were done with 33 participants of the Owners, Top Management, and Managers of MSMEs’ Foods and Drinks sectors through a non-probability of purposive sampling method, based on the regional sampling criteria of the four highest number of Food and Beverage MSMEs providers (West, East, and Central Java, also Jakarta). The results show that the effectiveness of Entrepreneurship Digitalization is determined by High-Skilled Human Resources, Digital Technology, and organizational management, which create Digital innovation, Sustainable Completeness, and Performance Growth, supporting the extended theory of Resources-Based, integrated with the Diffusion of Innovation, as a new model research agenda. Keywords: Entrepreneurship Digitalization Effectiveness, Digital Innovation, Sustainable Competitiveness, Sustainable Performance